Acerca de los impresos murcianos de los Cuentos morales de Marmontel - Amparo García Cuadrado (Mélanges de la Casa de Velázquez)
Taking as source the advertisements in the press of Madrid and the extant copies of Marmontel’s Moral Tales, this article analyses the circumstances surrounding the prosecution of this publishing venture. The study focuses on the shop in Murcia where the copies were printed between 1787 and 1789.